(untitled) (Swiss Medical Weekly, 2012)
Despite progress made in the field of immunosuppression, graft rejection remains a major cause of morbidity and mortality of patients after solid organ transplantation. There are several genetic causes which could influence the outcome of renal transplantation. One of the main determining factors of success in renal transplantation is human leukocyte antigen (HLA) compatibility between donor and recipient, particularly at HLA-A, HLA-B and HLA-DR loci. HLA compatibility remains an essential immunological barrier, despite modern immunosuppressive treatments. There is also evidence that natural killer (NK) cell alloreactivity contributes to the immune response which modulates the outcome of renal transplantation. However, the clinical impact of combinations of KIR genes (family of NK cell receptors) and their HLA ligands in donor and recipient still remains to be clearly established. Furthermore, cytokines are involved in the immune reaction against the renal transplant, but the implication of the genetic polymorphism of cytokines is strongly debated. Therefore, while HLA compatibility remains a primordial component for any renal transplantation, it would be premature to use the two other genetic aspects as criteria for organ allocation and as prognostic factors.